COVID-19 Patient Psychological Pain Factors - Zhengkai, Niu; Yajing, Shen (Frontiers in Psychology, 2021)
The level of psychological pain in patients with COVID-19 was investigated in this study by hypothesis testing, one-way ANOVA, multi factor ANOVA, and correlation analysis. The psychological pain thermometer and post-traumatic growth assessment scale were used as research tools. Many factors appear to influence the psychological state of COVID-19 patients including practical problems, communication problems, emotional problems, physical problems, and psychiatric/relative concerns. The severity of the disease, the surrounding environment, family health problems, life perceptions, interpersonal relationships, personal strength, mental changes, new possibilities, and the total post-traumatic growth score are also affected. There is a significant negative correlation between psychological pain and post-traumatic growth. There are significant differences in the degree of psychological pain across the demographic data. Practical problems, communication problems, emotional problems, physical problems, and spiritual/religious concerns show significant effects on the degree of psychological pain.